Calculation of additional shunt for current sensor of insulators - N. A. Tereshchenko; K. I. Nikitin; M. A. Kholmov; V. I. Novoselov (Омский научный вестник)
The purpose of the study is to review the existing devices and methods for diagnosing and monitoring the state of high-voltage insulation, which plays an important role in the criteria for the reliability of the power system. One of the main methods for diagnosing insulators is a visual inspection. At the moment, online methods have become widespread, allowing to fix the process of destruction of insulation under voltage. Despite the existence of various methods and devices, the problem of timely detection of insulation deterioration in the operating mode has not been solved at the moment. This problem is solved by using an additional shunt design. When the task is achieved, the method of calculating the strength analysis of the additional shunt is used, and the simulation of this process is performed in the ANSYS program. Mechanical strength sufficient for operation under voltage. Experimental tests are carried out with the developed sample of the shunt. As a result of the study, a number of experiments are carried out with this design of the shunt, which have confirmed its performance. Due to the presence of the shunt, it is possible to fix leakage currents of the order of several tens of microamperes. Thus, the authors have proposed the current sensor, which is made in the form of an additional resistive shunt.